Turbulent rectangular ducts with minimum secondary flow - Vidal, A.; Vinuesa, Ricardo; Schlatter, Philipp; Nagib, H. M. (International Journal of Heat and Fluid Flow, 2018)
In the present study we perform direct numerical simulations (DNSs) of fully-developed turbulent rectangular ducts with semi-cylindrical side-walls at Reτ c ≃ 180 with width-to-height ratios of 3 and 5. The friction Reynolds number Reτ c is based on the centerplane friction velocity and the half-height of the duct. The results are compared with the corresponding duct cases with straight side-walls (Vinuesa et al., 2014), and also with spanwise-periodic channel and pipe flows. We focus on the influence of the semi-cylindrical side-walls on the mean cross-stream secondary flow and on further characterizing the mechanisms that produce it. The role of the secondary and primary Reynolds-shear stresses in the production of the secondary flow is analyzed by means of quadrant analysis and conditional averaging. Unexpectedly, the ducts with semi-cylindrical side-walls exhibit higher cross-flow rates and their secondary vortices relocate near the transition point between the straight and curved walls. This behavior is associated to the statistically preferential arrangement of sweeping events entering through the curved wall and ejections arising from the adjacent straight wall. Therefore, the configuration with minimum secondary flow corresponds to the duct with straight side-walls and sharp corners. Consequences on experimental facilities and comparisons between experiments and various numerical and theoretical models are discussed revealing the uniqueness of pipe flow.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Direct numerical simulation; Secondary flow; Side-wall geometry; Turbulent duct flow; Wall-bounded turbulence